Fluorescent energy transfer causing misleading signal in multicolor flow cytometry. Issue 11 (7th April 2021) - Khenine, Hana; Waeckel, Louis; Seghrouchni, Fouad; Berger, Anne‐Emmanuelle; Lambert, Claude
Abstract: Multiple immunolabeling introduces high risks of interferences between fluorochromes. In an intend to analyze T cell clonality using CD3‐APC Alexa750, CD4‐Pac Blue, CD8‐Krome Orange, CD56‐PE‐Cy7 and Vbeta clonotypes FITC and PE, we repeatedly observed a clear, unexpected signal on B770 (PE‐Cy7) detector on the Vb subset mimicking a lymphoproliferative disorder. The aim of this study was to identify and prevent this source of artifact. The study was performed on a seven color panel performed on fresh whole blood, labeled, fixed, lyzed and analyzed on Navios Cytometer Beckman Coulter. Data were reanalyzed using Kaluza. Eleven tubes tested two clonotypes each with the same T cell backbone. Only one representative combination is presented. Using this panel, we observed repeatedly a strong CD56 PE‐Cy7 (B755 LP) on all Vbeta1 T cell subsets but not on Vbeta 2‐FITC T cells. The effect was still observed after removing CD56‐PE‐Cy7 (Full Minus One). Changing anti‐CD3 APC‐Alexa 750 with CD3APC, the B755 LP signal disappeared but a B695/30 signal appeared. Shifting to CD3‐FITC abolished any unexpected red signal. This demonstrates a fluorescent energy transfer (FRET) between PE excited by the blue laser and Alexa750 to be excited by the red laser. Accordingly, the Vbeta PE fluorescence intensity was reduced when FRET happened and clearly increased when CD3‐FITC was used instead. This observation clearly reminds that FRET can give misleading results in case of labeling of very close markers with complementary fluorochromes. This risk has to be considered in panel design.